Peran Kualitas Pelayanan Customer Service Dalam Meningkatkan Loyalitas Nasabah Bri Unit Kalisat - Septiana Malihah; Refi Anggraini; M.F.Hidayatullah . (CV. ITTC INDONESIA, 2026)
The rapid development of technology and intense competition in the banking sector require every financial institution to provide superior service to maintain business continuity. The quality of service provided by Customer Service, as the frontline, is a determining factor in building a positive image and public trust. This study aims to analyze the role of customer service quality at BRI Kalisat Unit based on the dimensions of reliability, responsiveness, assurance, empathy, and tangibles. It also identifies key indicators that determine customer satisfaction and loyalty during direct interactions with customer service. It also examines the challenges faced in providing responsive and quality service. This study applies a qualitative method with a descriptive approach to accurately describe the phenomena in the field. Data were collected through in-depth interviews with research subjects consisting of customer service and customers, supplemented by literature studies as a secondary data source. The data analysis process includes data reduction, presentation, and drawing conclusions. The results show that service quality at BRI Kalisat Unit is in the good category and significantly strengthens customer loyalty. Key indicators that encourage customer loyalty include polite, communicative officers, and the ability to provide clear solutions. However, there are operational challenges such as low customer digital literacy and technical system disruptions that sometimes hamper service speed. In conclusion, despite facing technical obstacles and limited customer digital literacy, strengthening interpersonal skills and updating technology systems are strategic implications that must be implemented. Continuous improvement efforts will ensure customer loyalty and prevent future switching to competitors.